Photoaffinity labeling of indole-3-acetic acid-binding proteins in maize - Jones, Alan M. (1989)
The photoaffinity labeling agent 5-azidoindole-3-acetic acid, an analog of the endogenous plant hormone indole-3-acetic acid (an auxin), was used to identify indole-3-acetic acid-binding proteins in maize. Two peptides with subunit molecular masses of 24 and 22 kilodaltons are specifically labeled in a saturable manner. Both peptides are slightly acidic and behave as dimers under nondenaturing conditions. The possibility that one of these peptides is the auxin receptor that mediates cell elongation in maize is discussed.